R.N. (Realidad ng Nars): A video documentary on Filipino nurses working in other field - Banaga, Marionne P. (Animo Repository, 2012)
The number of Filipino Registered Nurses (RNs) that are underemployed has been increasing at an alarming rate since 2001. According to the data given by the Professional Regulation Commission, there were a total of 67, 220 newly licensed nurses from the 154 107 nursing hopefuls in 2008 and most of them are underemployed. This documentary aimed to find out (1) what factors make Filipino Registered Nurses retain/leave their non-nursing-related jobs, and (2) do they still opt to pursue a nursing- related career in the future. It was found out that the fundamental reason why RNs decided to stay in their non-nursing-related job is because of Herzberg's Hygiene Factor-salary, to be more specific and when given the chance, they will pursue nursing still.